The software defined implantable modular platform (STELLA) for preclinical deep brain stimulation research in rodents. (21st September 2021) - Plocksties, Franz; Kober, Maria; Niemann, Christoph; Heller, Jakob; Fauser, Mareike; Nüssel, Martin; Uster, Felix; Franz, Denise; Zwar, Monique; Lüttig, Anika; Kröger, Justin; Harloff, Jörg; et al.
Abstract: Context. Long-term deep brain stimulation (DBS) studies in rodents are of crucial importance for research progress in this field. However, most stimulation devices require jackets or large head-mounted systems which severely affect mobility and general welfare influencing animals' behavior. Objective. To develop a preclinical neurostimulation implant system for long-term DBS research in small animal models. Approach. We propose a low-cost dual-channel DBS implant called software defined implantable platform (STELLA) with a printed circuit board size of Ø13 × 3.3 mm, weight of 0.6 g and current consumption of 7.6 µ A/3.1 V combined with an epoxy resin-based encapsulation method. Main results. STELLA delivers charge-balanced and configurable current pulses with widely used commercial electrodes. While in vitro studies demonstrate at least 12 weeks of error-free stimulation using a CR1225 battery, our calculations predict a battery lifetime of up to 3 years using a CR2032. Exemplary application for DBS of the subthalamic nucleus in adult rats demonstrates that fully-implanted STELLA neurostimulators are very well-tolerated over 42 days without relevant stress after the early postoperative phase resulting in normal animal behavior. Encapsulation, external control and monitoring of function proved to be feasible. Stimulation with standard parameters elicited c-Fos expression by subthalamic neurons demonstrating biologically active function of STELLA. Significance. We developed a fully implantable, scalable and reliable DBS device that meets the urgent need for reverse translational research on DBS in freely moving rodent disease models including sensitive behavioral experiments. We thus add an important technology for animal research according to 'The Principle of Humane Experimental Technique'—replacement, reduction and refinement (3R). All hardware, software and additional materials are available under an open source license.